Extending the Duration of Artemether-Lumefantrine Treatment for Uncomplicated Plasmodium falciparum Malaria: Updated US Centers for Disease Control and Prevention Guidance Based on Review of Surveillance, Consultations, and Published Data - Jimee Hwang; Eric S Halsey; Mateusz M Plucinski; Joel L N Barratt; Julie R Gutman; Michelle A Chang; Seymour G Williams; Kimberly E Mace; Jessica T Lin; Philip J Rosenthal; Sunil Parikh; Alison D Ridpath (Clinical Infectious Diseases, 2026)
Abstract Background Artemisinin-based combination therapies (ACTs) are recommended for treatment of uncomplicated Plasmodium falciparum malaria; artemether-lumefantrine (AL) is the only ACT available in the United States. Reports of AL treatment failure among international travelers raise concerns about the continued adequacy of the standard 3-day AL regimen for travelers. Methods We reviewed US malaria surveillance data, clinical consultation records, and antimalarial molecular resistance surveillance data at the Centers for Disease Control and Prevention (CDC). We also conducted a literature review and meta-analysis to assess the risk of treatment failure following treatment with AL or atovaquone-proguanil (AP) in travelers treated in nonendemic settings and reviewed the efficacy and safety of AL regimens with durations longer than the standard 3-day (6-dose) course. Results From November 2022 through October 2025, CDC was consulted on 47 P. falciparum treatment failures, including 40 following AL-based and 7 following AP-based treatments. All reported travel to Africa, and 62% presented with severe malaria. Among AL failures, 85% were late recrudescences occurring 1–8 weeks after initial treatment. In the meta-analysis, the pooled AL treatment failure risk was higher for data collected in 2018 or later (7% [95% CI, 1%–32%]) compared to before 2018 (4% [95% CI, 2%–8%]), although the difference was not statistically significant (P = .3). Extended AL regimens, particularly a 5-day (10-dose) course, were well tolerated and consistently achieved higher lumefantrine exposure. Conclusions These findings informed updated CDC guidance recommending an extended 5-day (10-dose) course of AL for treating uncomplicated P. falciparum malaria in the United States.